The Effect of Manufacturing Technology Type on Cost Structure: Evidence from Egypt - Mohamed E. Abulezz; Ramy G. Sherief (STIE Malangkucecwara, 2020)
We investigate the effect of manufacturing technology type on cost structure in Egypt. We argue that firms adopting advanced manufacturing technology are associated with less rigid and more flexible cost structures. A sample of 40 Egyptian manufacturing firms listed on EGX over a 6-year period (2011-2016), producing 240 company-year observations is tested. Overall, evidence supports the view that firms with advanced manufacturing technologies have more flexible cost structure. The result is robust to alternative specifications by replacing cost of goods sold (COGS) by operating expenses and introducing firm size as a control variable. Our finding continues to hold after robustness tests. Our finding is expected to fill up a gap in the extant literature in two ways. First, this study provides evidence on the effect of manufacturing technology type on cost structure in a developing country (i.e., Egypt). Second, unlike the extant literature, which predominately uses case study and refer to anecdotal evidence, the presumed relation between the manufacturing technology type and the cost structure is systematically examined in a cross-sectional design. Thus, the research findings may be more generalizable.